2012
DOI: 10.1007/s00234-012-1081-1
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional susceptibility-weighted imaging at 7 T using fractal-based quantitative analysis to grade gliomas

Abstract: The present study confirms that SWI at 7 T is a useful method for detecting intratumoral vascular architecture of brain gliomas and that SWI pattern quantification by means of fractal dimension offers a potential objective morphometric image biomarker of tumor grade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 28 publications
1
50
0
2
Order By: Relevance
“…Fractal studies on images of malignant tissues have revealed an increase in fractal dimension in malignant v.s normal tissue and an increase in fractal dimension/complexity with tumor grade in many different forms of cancer including brain [50,51], breast [52,53], cervical [52,54] and hepatocellular carcinomas [55]. These studies demonstrate the clinical potential of fractal analysis in the diagnosis and grading of malignant tumors.…”
Section: Cancermentioning
confidence: 79%
See 4 more Smart Citations
“…Fractal studies on images of malignant tissues have revealed an increase in fractal dimension in malignant v.s normal tissue and an increase in fractal dimension/complexity with tumor grade in many different forms of cancer including brain [50,51], breast [52,53], cervical [52,54] and hepatocellular carcinomas [55]. These studies demonstrate the clinical potential of fractal analysis in the diagnosis and grading of malignant tumors.…”
Section: Cancermentioning
confidence: 79%
“…Moreover, fractal studies have demonstrated a decrease in fractal dimension of the CNS with illness (i.e., Alzheimer's [42], epilepsy [23,24], MS [45], stroke [49]) which correlates with metabolic studies demonstrating a decline in glucose metabolism with illness [83,85,88,[90][91][92][93][94][95][96][97][101][102][103]. Conversely, there are diseases which demonstrate an increase in fractal dimension including cancer [50][51][52][53][54][55] and grey matter structural changes in MS [46]. Of significance, these diseases which demonstrate an increase in fractal dimension also demonstrate an increase in glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations